2011
DOI: 10.1094/pdis-02-11-0080
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phenotypic Characterization of Colletotrichum Species Associated with Anthracnose Disease of Papaya in Trinidad

Abstract: Anthracnose disease is a major limiting factor to papaya production worldwide. Accurate identification of the pathogens responsible for this disease is important to developing disease management strategies. One hundred and three (103) isolates of Colletotrichum were collected from infected papaya fruits cvs. Red lady and Tainung No. 2 - F1 hybrid in Trinidad. Of all isolates, 79% were C. gloeosporioides and 21% were C. truncatum. Spore morphology, cultural characteristics, differential reaction to benomyl in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 55 publications
1
15
0
7
Order By: Relevance
“…The analysis also showed that location, banana cultivar and morphotype did not contribute to phylogenetic relatedness. The results were similar to those of a study by Rampersad (2011) on papaya anthracnose in which geographical distribution, host cultivar or morphotype was not an indication of the phylogenetic relatedness of the papaya isolates. C. gloeosporioides and C. musae are part of the taxa in C. gloeosporioides species complex in which the species in this complex has broad genetic and biological diversity (Damm et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The analysis also showed that location, banana cultivar and morphotype did not contribute to phylogenetic relatedness. The results were similar to those of a study by Rampersad (2011) on papaya anthracnose in which geographical distribution, host cultivar or morphotype was not an indication of the phylogenetic relatedness of the papaya isolates. C. gloeosporioides and C. musae are part of the taxa in C. gloeosporioides species complex in which the species in this complex has broad genetic and biological diversity (Damm et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…The findings of this study have an important bearing on the epidemiology of anthracnose disease since different species of Colletotrichum may have different conidial dispersal capacities (Ntahimpera et al, 1999;Rampersad, 2011). Accurate identification of the anthracnose-causing pathogen is also important, since different species of Colletotrichum may vary in their reaction to different types of fungicides (Rampersad, 2011).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fruit production is mostly affected in both high-value crops and wild fruits in natural habitats. However, Colletotrichum species associated with wild fruits are poorly known [4,5]. Colletotrichum specie was voted as the eighth most important plant pathogens in the world in a recent survey among fungal pathologists, for its perceived scientific and economic importance [6].…”
Section: Introductionmentioning
confidence: 99%
“…As espécies pertencentes ao gênero, geralmente são responsáveis pela antracnose e outras doenças em uma grande variedade de culturas incluindo cereais, leguminosas, olerícolas e frutos [3][4][5][6].…”
Section: Introductionunclassified